HUBUNGAN ANTARA LINGKUNGAN ISLAMI DENGAN PEMBENTUKAN AKHLAKUL KARIMAH PADA ANAK USIA DINI - Amalia Abdiah, Nor (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The development of akhlakul karimah (noble character) in early childhood is a fundamental pillar of character education. An Islamic environment comprising a religious atmosphere, teacher role models, and a culture of Islamic values is considered instrumental in the internalization of moral values in children. This study aims to examine the relationship between the Islamic environment and akhlakul karimah in early childhood, introducing a methodological novelty through the use of standardized psychometric instruments grounded in Islamic theory and the Indonesian Regulation Permendikbudristek No. 16 of 2022. Employing a quantitative correlational approach, the study involved 60 children aged 5–6 years from three early childhood education institutions (PAUD) in Hulu Sungai Selatan. Data were collected using two validated and reliable Likert scales: the Islamic Environment Scale and the Akhlakul Karimah Scale. Pearson correlation analysis revealed a significant positive relationship between the Islamic environment and akhlakul karimah (r = 0.611; p < 0.01). These findings highlight the importance of a structured Islamic environment in shaping children's character. The study offers practical contributions to strengthening Islamic value-based PAUD strategies through teacher training, religious cultural integration, and parental involvement. Further research is recommended using longitudinal designs and multi-perspective approaches. ABSTRAK Pembentukan akhlakul karimah sejak usia dini merupakan fondasi utama dalam pendidikan karakter. Lingkungan Islami yang meliputi suasana religius, keteladanan guru, dan budaya nilai Islami diperkirakan berperan penting dalam internalisasi nilai moral pada anak. Penelitian ini bertujuan menguji hubungan antara lingkungan Islami dan akhlakul karimah pada anak usia dini dengan kebaruan metodologis berupa penggunaan instrumen psikometrik terstandar berdasarkan teori Islam dan Permendikbudristek No. 16 Tahun 2022. Menggunakan pendekatan kuantitatif korelasional, penelitian ini melibatkan 60 anak usia 5–6 tahun dari tiga PAUD di Hulu Sungai Selatan. Data diperoleh melalui dua skala Likert yang valid dan reliabel: Skala Lingkungan Islami dan Skala Akhlakul Karimah. Hasil analisis Pearson menunjukkan hubungan positif signifikan antara lingkungan Islami dan akhlakul karimah (r = 0,611; p < 0,01). Temuan ini menggarisbawahi pentingnya desain lingkungan Islami yang sistematis dalam membentuk karakter anak. Penelitian ini memberikan kontribusi praktis bagi penguatan strategi PAUD berbasis nilai Islam melalui pelatihan guru, pembudayaan religius, dan pelibatan orang tua. Studi lanjutan disarankan dengan desain longitudinal dan pendekatan multi-perspektif.